Multivariate effect gradients driving forest demographic responses in the Iberian Peninsula - Coll, Marta; Penuelas, Josep; Ninyerola, Miquel; Pons, Xavier; Carnicer, Jofre (Forest Ecology and Management, 2013)
A precise knowledge of forest demographic gradients in the Mediterranean area is essential to assess future impacts of climate change and extreme drought events. Here we studied the geographical patterns of forest demography variables (tree recruitment, growth and mortality) of the main species in Spain and assessed their multiple ecological drivers (climate, topography, soil, forest stand attributes and tree-spe- cific traits) as well as the geographical variability of their effects and interactions. Quantile modeling analyses allowed a synthetic description of the gradients of multiple covariates influencing forest demog- raphy in this area. These multivariate effect gradients showed significantly stronger interactions at the extremes of the rainfall gradient. Remarkably, in all demographic variables, qualitatively different levels of effects and interactions were observed across tree-size classes. In addition, significant differences in demographic responses and effect gradients were also evident between the dominant genus Quercus and Pinus. Quercus species presented significantly higher percentage of plots colonized by new recruits, whereas in Pinus recruitment limitation was significantly higher. Contrasting positive and negative growth responses to temperature were also observed in Quercus and Pinus, respectively. Overall, our results synthesize forest demographic responses across climatic gradients in Spain, and unveil the inter- actions between driving factors operating in the drier and wetter edges.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Forest demography; Growth; Macroecology; mortality; Quantile modeling; Recruitment

Direct and indirect landscape effects on Quercus ilex regeneration in heterogeneous environments. - Puerta-Piñero, Carolina; Pino, Joan; Gómez, José María (Oecologia, 2012)
Understanding how plant-animal interactions shape plant regeneration is traditionally examined at local scales. In contrast, landscape ecologists working at regional scales often have to infer the mechanisms underlying vegetation patterns. In this study, we empirically explored how landscape attributes (patch connectivity, size, shape, irradiance, slope, and elevation) influence biotic interactions in 1- and 2-year seedlings and saplings of Quercus ilex. We combined field data and GIS-based information under a set of five connectivity scenarios, presuming low, intermediate, and long-distance seed dispersal. Our study emphasizes that landscape, apart from its direct effects on plants, plays a key, albeit indirect, role in plant demography through its effects on seed dispersers and predators. Moreover, the effects of landscape on recruitment differed between plant life stages. One-year seedlings and saplings appear to depend more on plant-animal interactions, while 2-year seedlings depend more on irradiance. Differences in patch connectivity resulted in direct and indirect effects on biotic interactions, which, in turn, produced contrasting positive and negative effects on regeneration at different stages of the life cycle. While jays and wild boars seem crucial to all life stages and most of the connectivity scenarios, rodents and herbivores affected only 1-year seedlings and saplings, respectively, and only a few of the connectivity scenarios. By simultaneously including an ensemble of explanatory factors, our study emphasizes that regeneration depends on a set of key drivers, both abiotic (i.e. irradiance) and biotic (i.e. jays and wild boars), whose effects are greatly modulated by landscape traits.
Keywords: Animals; Ecosystem; irradiance; landscape connectivity; Life Cycle Stages; Mediterranean; Passeriformes; Plant Dispersal; Plant–animal interactions; Quercus; Quercus: growth & development; Recruitment; Seedling; Seedling: growth & development; Sus scrofa

Sporadic rainy events are more critical than increasing of drought intensity for woody species recruitment in a Mediterranean community. - Matías, Luis; Zamora, Regino; Castro, Jorge (Oecologia, 2012)
The understanding of the impact of extreme climatic events under a global climate change scenario is crucial for the accurate forecast of future plant community dynamics. We have experimentally assessed the effect of drier and wetter summer conditions on the recruitment probabilities and the growth of seedlings from eight woody species representative of the most important functional groups in the community, pioneer shrubs, mid-successional shrubs and trees, across the main habitats in the study area (open habitat, shrubland, and forest). Our hypothesis proposes that wet summer conditions would represent a good opportunity for tree species regeneration, enhancing both forest maintenance and expansion. A drier summer scenario, on the other hand, would limit forest regeneration, and probably hinder the colonization of nearby habitats. We found a habitat effect on the emergence, survival, and final biomass, whereas different climate scenarios affected seedling survival and biomass. A wet summer boosted growth and survival, whereas greater drought reduced survival only in some cases. These results were modulated by the habitat type. Overall, shrub species presented higher survival and growth and were less affected by more severe drought, whereas some tree species proved to be extremely dependent on wet summer conditions. We conclude that the reduction in frequency of wet summers predicted for the coming decades in Mediterranean areas will have greater consequences for species recruitment than will increased drought. The different response of the species from the various functional groups has the potential to alter the composition and dominance of future plant communities.
Keywords: Angiosperms; Angiosperms: growth & development; climate change; Droughts; Ecosystem; Mediterranean Region; Rain; rainfall variability; Recruitment; Seedling; Seedling: growth & development; Spain; summer drought; Vegetation dynamics

Drought-Induced Multifactor Decline of Scots Pine in the Pyrenees and Potential Vegetation Change by the Expansion of Co-occurring Oak Species - Galiano, L.; Martínez-Vilalta, J.; Lloret, F. (Ecosystems, 2010)
Episodes of drought-induced tree dieback have been recently observed in many forest areas of the world, particularly at the dry edge of species distributions. Under climate change, those effects could signal potential vegetation shifts occurring over large geographical areas, with major impacts on ecosystem form and function. In this article, we studied the effect of a single drought episode, which occurred in summer 2005, on a Scots pine population in central Pyrenees (NE Spain). Our main objective was to study the environmental correlates of forest decline and vegetation change at the plot level. General and generalized linear models were used to study the relationship between canopy defoliation, mortality and recruitment, and plot characteristics. A droughtdriven multifactor dieback was observed in the study forest. Defoliation and mortality were associated with the local level of drought stress estimated at each plot. In addition, stand structure, soil properties, and mistletoe infection were also associated with the observed pattern of defoliation, presumably acting as long-term predisposing factors. Recruitment of Scots pine was low in all plots. In contrast, we observed abundant recruitment of other tree species, mostlyQuercus ilexand Q. humilis, particularly in plots where Scots pine showed high defoliation and mortality. These results suggest that an altitudinal upwards migration of Quercusspecies, mediated by the dieback of the currently dominant species, may take place in the studied slopes. Many rear-edge populations of Scots pine sheltered in the mountain environments of the Iberian Peninsula could be at risk under future climate scenarios.
Keywords: canopy defoliation; Drought; mistletoe; mortality; pinus sylvestris l; Recruitment; scots pine; scots pine (Pinus sylvestris L.); soil properties; Stand Structure; summer; summer water availability; Water availability

The future of scattered trees in agricultural landscapes. - Gibbons, P; Lindenmayer, D B; Fischer, J; Manning, a D; Weinberg, A; Seddon, J; Ryan, P; Barrett, G (Conservation biology : the journal of the Society for Conservation Biology, 2008)
Mature trees scattered throughout agricultural landscapes are critical habitat for some biota and provide a range of ecosystem services. These trees are declining in intensively managed agricultural landscapes globally. We developed a simulation model to predict the rates at which these trees are declining, identified the key variables that can be manipulated to mitigate this decline, and compared alternative management proposals. We used the initial numbers of trees in the stand, the predicted ages of these trees, their rate of growth, the number of recruits established, the frequency of recruitment, and the rate of tree mortality to simulate the dynamics of scattered trees in agricultural landscapes. We applied this simulation model to case studies from Spain, United States, Australia, and Costa Rica. We predicted that mature trees would be lost from these landscapes in 90-180 years under current management. Existing management recommendations for these landscapes--which focus on increasing recruitment--would not reverse this trend. The loss of scattered mature trees was most sensitive to tree mortality, stand age, number of recruits, and frequency of recruitment. We predicted that perpetuating mature trees in agricultural landscapes at or above existing densities requires a strategy that keeps mortality among established trees below around 0.5% per year, recruits new trees at a rate that is higher than the number of existing trees, and recruits new trees at a frequency in years equivalent to around 15% of the maximum life expectancy of trees. Numbers of mature trees in landscapes represented by the case studies will decline before they increase, even if strategies of this type are implemented immediately. This decline will be greater if a management response is delayed.
Keywords: agricultural-landscape trees; management of scattered trees; paddock trees; Recruitment; scattered- tree ecosystems; set-aside forest; tree decline; tree patches

The future of scattered trees in agricultural landscapes. - Gibbons, P.; Lindenmayer, D. B.; Fischer, J.; Manning, a D.; Weinberg, A.; Seddon, J.; Ryan, P.; Barrett, G. (Conservation biology : the journal of the Society for Conservation Biology, 2008)
Mature trees scattered throughout agricultural landscapes are critical habitat for some biota and provide a range of ecosystem services. These trees are declining in intensively managed agricultural landscapes globally. We developed a simulation model to predict the rates at which these trees are declining, identified the key variables that can be manipulated to mitigate this decline, and compared alternative management proposals. We used the initial numbers of trees in the stand, the predicted ages of these trees, their rate of growth, the number of recruits established, the frequency of recruitment, and the rate of tree mortality to simulate the dynamics of scattered trees in agricultural landscapes. We applied this simulation model to case studies from Spain, United States, Australia, and Costa Rica. We predicted that mature trees would be lost from these landscapes in 90-180 years under current management. Existing management recommendations for these landscapes--which focus on increasing recruitment--would not reverse this trend. The loss of scattered mature trees was most sensitive to tree mortality, stand age, number of recruits, and frequency of recruitment. We predicted that perpetuating mature trees in agricultural landscapes at or above existing densities requires a strategy that keeps mortality among established trees below around 0.5% per year, recruits new trees at a rate that is higher than the number of existing trees, and recruits new trees at a frequency in years equivalent to around 15% of the maximum life expectancy of trees. Numbers of mature trees in landscapes represented by the case studies will decline before they increase, even if strategies of this type are implemented immediately. This decline will be greater if a management response is delayed.
The following values have no corresponding Zotero field: accession-num: 18680500
Keywords: agricultural-landscape trees; management of scattered trees; paddock trees; Recruitment; scattered- tree ecosystems; set-aside forest; tree decline; tree patches

Influence of forest structure and environmental variables on recruit survival and performance of two Mediterranean tree species (Quercus faginea L. and Q. suber Lam.) - Maltez-Mouro, Sara; García, Luis V.; Freitas, Helena (European Journal of Forest Research, 2008)
We investigated the regeneration requirements of the two dominant tree species in a mixed-oak forest of SW Portugal: Quercus suber (cork oak, evergreen) and Q. faginea (Portuguese oak, winter-deciduous). We hypothesized that (1) recruits of diVerent oak species are diVerentially inXuenced by soil and overstory variables and (2) diVerent factors explain the recruitment occurrence and performance of the same species. We sampled the recruits’ height and diameter, and several environmental and forest structure variables of their microsites. Both recruitment occurrence and performance were modeled using generalized linear models. Our Wnal models predicted the probability of occurrence of recruits of Q. faginea and Q. suber with 74 and 82% of accuracy, respectively, and explained about 50% of the variance of their recruitment performance. The recruits of Q. faginea tended to occur in microsites with higher canopy height, canopy density and litter cover, and closer to both conspeciWc and heterospeciWc adults, while the opposite was true for recruits of Q. suber. The performance of recruits of Q. suber was favored by the higher litter cover (a good surrogate for N and P availability), but negatively aVected by the higher litter depth. We concluded the following: (1) there were signiWcantly diVerent regeneration niches for each species (Q. faginea and Q. suber); (2) the factors explaining the recruitment occurrence diVered from those explaining the recruitment performance; (3) the overstory plays a complex and important role in the regeneration process; (4) diVerent variables apparently related with the same environmental factor (e.g. litter cover and litter depth) could aVect recruits in an opposite way; (5) sensitive trade-oVs must be considered for delineating management actions, since they could favor the regeneration of Q. suber, but, at the same time, negatively aVect the regeneration of Q. faginea.
Keywords: evergreen oak; litter e v ects; litter effects; mediterranean forest; Recruitment; winter-deciduous oak

Influence of forest structure and environmental variables on recruit survival and performance of two Mediterranean tree species (Quercus faginea L. and Q. suber Lam.) - Maltez-Mouro, Sara; García, Luis V.; Freitas, Helena (European Journal of Forest Research, 2008)
We investigated the regeneration requirements of the two dominant tree species in a mixed-oak forest of SW Portugal: Quercus suber (cork oak, evergreen) and Q. faginea (Portuguese oak, winter-deciduous). We hypothesized that (1) recruits of diVerent oak species are diVerentially inXuenced by soil and overstory variables and (2) diVerent factors explain the recruitment occurrence and performance of the same species. We sampled the recruits’ height and diameter, and several environmental and forest structure variables of their microsites. Both recruitment occurrence and performance were modeled using generalized linear models. Our Wnal models predicted the probability of occurrence of recruits of Q. faginea and Q. suber with 74 and 82% of accuracy, respectively, and explained about 50% of the variance of their recruitment performance. The recruits of Q. faginea tended to occur in microsites with higher canopy height, canopy density and litter cover, and closer to both conspeciWc and heterospeciWc adults, while the opposite was true for recruits of Q. suber. The performance of recruits of Q. suber was favored by the higher litter cover (a good surrogate for N and P availability), but negatively aVected by the higher litter depth. We concluded the following: (1) there were signiWcantly diVerent regeneration niches for each species (Q. faginea and Q. suber); (2) the factors explaining the recruitment occurrence diVered from those explaining the recruitment performance; (3) the overstory plays a complex and important role in the regeneration process; (4) diVerent variables apparently related with the same environmental factor (e.g. litter cover and litter depth) could aVect recruits in an opposite way; (5) sensitive trade-oVs must be considered for delineating management actions, since they could favor the regeneration of Q. suber, but, at the same time, negatively aVect the regeneration of Q. faginea.
Keywords: evergreen oak; litter e v ects; litter effects; mediterranean forest; Recruitment; winter-deciduous oak

Establishment of co-existing Mediterranean tree species under a varying soil moisture regime - Lloret, Francisco; Penuelas, Josep; Ogaya, Romà (Journal of Vegetation Science, 2004)
We investigated the responses of two co-existing Mediterranean trees with different regeneration strategies (Phillyrea latifolia seedlings and Quercus ilex sprouts) to experimental drought below the forest canopy. We considered different recruitment stages and used leaf isotopic discrimination to estimate water use efficiency (WUE) and nitrogen availability and use. Drought decreased the emergence and survival of seedlings and sprouts. Survival and growth of older saplings were not influenced by drought. Seedling emergence of P. latifolia was higher than Q. ilex sprout production, but Q. ilex sprouts had higher survival and growth rates. These differences disappeared in the sapling stage. Carbon isotopic discrimination suggested that Q. ilex sprouts had higher WUE than P. latifolia seedlings. Drought increased WUE of recruits, particularly in Q. ilex. Water use regulation increased with ageing, particularly in P. latifolia. Q. ilex had higher δ15N values than P. latifolia; these were also higher under drier soil conditions. Current year seedlings had higher δ15N than saplings, particularly in P. latifolia, suggesting they exploit superficial soil layers. These results suggest that sprouts obtain benefit from resources stored in parent plants. At earlier stages, they perform better than seedlings. This response is not coupled to adult vulnerability to drought for these species, revealing the difficulty of predicting species dynamics during climate change.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: climate change; Drought; mediterranean forest; Nitrogen use; phillyrea latifolia; Quercus ilex; Recruitment; Regeneration; Seedling; sprouting; water use efficiency

A global change-induced biome shift in the Montseny mountains (NE Spain) - Penuelas, Josep; Boada, Martí (Global Change Biology, 2003)
Shifts in plant species and biome distribution in response to warming have been described in past climate changes. However, reported evidence of such shifts under current climate change is still scarce. By comparing current and 1945 vegetation distribution in the Montseny mountains (Catalonia, NE Spain), we report here a progressive replacement of cold-temperate ecosystems by Mediterranean ecosystems. Beech (Fagus sylvatica) forest has shifted altitudinally upwards by ca. 70 m at the highest altitudes (1600–1700 m). Both the beech forests and the heather (Calluna vulgaris) heathlands are being replaced by holm oak (Quercus ilex) forest at medium altitudes (800–1400 m). This beech replacement has been observed to occur through a progressive isolation and degradation of beech stands. In ‘isolated’ (small and surrounded by holm oaks) beech stands, beech trees are 30% more defoliated, beech recruitment is 41% lower, and holm oak recruitment is three times higher than in ‘continental’ (large and continuous) beech stands. The progressively warmer conditions, complemented by the land use changes (mainly the cessation of traditional land management) are the apparent causes, providing a paradigmatic example of global change affecting distributions of plant species and biomes.
The following values have no corresponding Zotero field: publisher: Blackwell Science, Ltd
Keywords: altitudinal shift; biome replacement; Calluna heathland; climate change; defoliation status; Fagus sylvatica; Land use change; mediterranean forest; Montseny mountains; Quercus ilex; Recruitment; temperate forest